2023
DOI: 10.1097/hjh.0000000000003422
|View full text |Cite
|
Sign up to set email alerts
|

The impact of blood pressure variability on cognition: current limitations and new advances

Abstract: Dementia is the most common neurodegenerative disease in the aging population. Emerging evidence indicates that blood pressure (BP) variability is correlated with cognitive impairment and dementia independent of mean BP levels. The state-of-the-art review summarizes the latest evidence regarding the impact of BP variability on cognition in cognitively intact populations, patients with mild cognitive impairment, and different dementia types, focusing on the important confounding factors and new advances. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 102 publications
(287 reference statements)
0
7
0
Order By: Relevance
“…Therefore, some of the older adult participants may have had mild cognitive impairment, which could affect the study findings. However, our older adult sample was comparable to many other BPV studies using community-based samples that may or may not have included individuals with mild cognitive impairment [8] , [26] , [59] . Nevertheless, BPV may be higher in those with mild cognitive impairment when compared to older adults with normal cognition [53] , at least when BPV is measured over longer time intervals.…”
Section: Discussionmentioning
confidence: 55%
“…Therefore, some of the older adult participants may have had mild cognitive impairment, which could affect the study findings. However, our older adult sample was comparable to many other BPV studies using community-based samples that may or may not have included individuals with mild cognitive impairment [8] , [26] , [59] . Nevertheless, BPV may be higher in those with mild cognitive impairment when compared to older adults with normal cognition [53] , at least when BPV is measured over longer time intervals.…”
Section: Discussionmentioning
confidence: 55%
“…Sequence-based metrics, including systolic and diastolic ARV, displayed the highest test-retest reliability in the overall sample. This is likely due to their decreased susceptibility to outliers and low-frequency oscillations in beat-to-beat BP compared to dispersion and instability BPV metrics ( 57 - 59 ). This concept is illustrated in Figure 3D - E , where we can see BP dispersion metrics, such as SD, are more heavily influenced by low-frequency oscillations in BP while BP ARV is more directly influenced by beat-to-beat changes in blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…24-hour and daytime BPV was related to dementia risk in the standard treatment group, whereas nighttime BPV was not associated with dementia risk in either group. There are few observational studies on ambulatory BPV and cognitive impairment/decline ( 1 , 42 ), and only one that directly compares 24-hour vs daytime vs nighttime BPV ( 25 ). Our findings with daytime BPV and not nighttime BPV are consistent with the study by McDonald et al, on relationships with cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, it is expected that some of these mechanisms are shared across time intervals of BPV, and more research will help pinpoint specific therapeutic targets. Much of the work linking BPV to dementia risk has relied on mid- to long-term BPV ( 1 , 42 ). Recent SPRINT post hoc analyses using clinic-based BPV measured over longer time intervals reported links with dementia risk in both the standard and intensive treatment groups ( 11 , 12 ), whereas the present study using 24-hour BPV via ambulatory monitoring only found associations in the standard treatment group.…”
Section: Discussionmentioning
confidence: 99%